Cytosolic proteome profiling of monocytes for male osteoporosis. Issue 3 (March 2017) - Zhu, W.; Shen, H.; Zhang, J-G.; Zhang, L.; Zeng, Y.; Huang, H-L.; Zhao, Y-C.; He, H.; Zhou, Y.; Wu, K-H.; Tian, Q.; Zhao, L-J.; et al.
Abstract Summary In male Caucasians with discordant hip bone mineral density (BMD), we applied the subcellular separation and proteome profiling to investigate the monocytic cytosol. Three BMD-associated proteins (ALDOA, MYH14, and Rap1B) were identified based on multiple omics evidence, and they may influence the pathogenic mechanisms of osteoporosis by regulating the activities of monocytes. Introduction Osteoporosis is a serious public health problem, leading to significant mortality not only in aging females but also in males. Peripheral blood monocytes (PBMs) play important roles in bone metabolism by acting as precursors of osteoclasts and producing cytokines important for osteoclast development. The first cytosolic sub-proteome profiling analysis was performed in male PBMs to identify differentially expressed proteins (DEPs) that are associated with BMDs and risk of osteoporosis. Methods Here, we conducted a comparative proteomics analysis in PBMs from Caucasian male subjects with discordant hip BMD (29 low BMD vs. 30 high BMD). To decrease the proteome complexity and expand the coverage range of the cellular proteome, we separated the PBM proteome into several subcellular compartments and focused on the cytosolic fractions, which are involved in a wide range of fundamental biochemical processes. Results Of the total of 3796 detected cytosolic proteins, we identified 16 significant (P  < 0.05) and an additional 22 suggestive (P  < 0.1) DEPs between samples with low vs. high hip BMDs. Some of the genes for DEPs, includingALDOA, MYH14, andRap1B, showed an association with BMD in multiple omics studies (proteomic, transcriptomic, and genomic). Further bioinformatics analysis revealed the enrichment of DEPs in functional terms for monocyte proliferation, differentiation, and migration. Conclusions The combination strategy of subcellular separation and proteome profiling allows an in-depth and refined investigation into the composition and functions of cytosolic proteome, which may shed light on the monocyte-mediated pathogenic mechanisms of osteoporosis.